Game Edukasi “Kids Learning” Sebagai Media Pembelajaran Dasar Untuk Anak Usia Dini Berbasis Android - Wanty Eka Jayanti; Eva Meilinda; Nana Fahriza (Jurnal Khatulistiwa Informatika, 2018)
Technology is one of today's lifestyles. With android, humans can get entertainment without having to go to a place, one of them through the game contained on android. Can not be denied many interesting and exciting game options to be played everyday at this time, but unfortunately the material contained in the game is more only intended for entertainment and minimum value is useful. For that reason researchers took the initiative to make the game "KIDS LEARNING" which contains elements and educational materials for young children. So when this game is played, the user can play as well as learn so as to change the idea that learning can be interesting and exciting. The game that researchers make is intended for early childhood to be a basic learning media to introduce Figures, Letters, Colors, Flats, Fruits, Animals, Vehicles and Planets. Game "KIDS LEARNING" Made with Game Engine Construct2. This game is an educational game where there is a menu of study and play menu. In the play menu there are Memory Match games, Counting, Guessing Animals and Guessing Color Balloons to sharpen the memory of the material that has been learned on the Learning Menu. game development has stages such as game design, display design and material selection contained in the game. This game is built to run on Android.